Fenomena Pembiasaan Penggunaan Baju Adat Lurik di SMAN 1 Gondang Tulungagung - Amur, Hamid Sulthon Al; Ito’, Ahmad Izzul (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to reveal the phenomenon of the habituation of wearing traditional lurik clothing as a form of local cultural preservation at SMAN 1 Gondang Tulungagung. This study is motivated by the issuance of Permendagri Number 10 of 2024, which encourages the use of regional clothing in the ASN and education environment. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects include student affairs representatives, teachers, and students. The results show that the habituation of wearing lurik is carried out consistently every first Friday of the month and on national holidays. The use of lurik traditional clothing is not only a cultural symbol but also a strategy for instilling values of local identity and nationalism in the school environment. This study concludes that the habituation strengthens cultural awareness, increases pride in regional identity, and strengthens the role of schools as agents of cultural preservation.